"Saying yes to everything": Slung Low's mission in a time of rapid change. (26th November 2019) - Perry, Rachel
Abstract : Purpose: This study explores what it means to be a mission-driven arts organisation (MDAO) in the UK. Drawing on literature relating to artistic risk and rupture, mission and vision, and arts participation, the purpose of this paper is to shed light on how Slung Low, a theatre organisation with a core staff of five, creates large and complex initiatives and seeks to make a difference to its local community. Design/methodology/approach: Using a case study approach, this interpretive study makes use of qualitative data to offer context-specific knowledge about how MDAOs create new initiatives including: interviews with members of the Slung Low team; attendance at company meetings; analysis of internal organisational documents, company website and artistic director's blog; and articles about Slung Low from the local, national and theatre industry press. Data was gathered through a research collaboration with Slung Low which is supported by Paul Hamlyn Foundation. Findings: The results offer fresh insight into how MDAOs take a positive approach to rupture and rapid change. The study finds that by embracing risk and committing to an ambitious and provocative mission, small-scale arts organisations can achieve artistic, cultural and social objectives which far exceed their size. Research limitations/implications: This paper offers an organisational perspective on the research questions and so participants were not interviewed on this occasion. However, the participant view will be the subject of further research with Slung Low. Originality/value: This research paper provides insight into one of the UK's most innovative theatre companies during a period of monumental change, and advances knowledge on mission-driven organisations by offering reflections on what it means to be an arts organisation which places rupture, risk and usefulness at the heart of its mission.